ANALISIS PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN - Rahardjo, Budi; Kristanto, Yunus Agung (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2024)
This research focuses on MSMEs with food and beverage products located in the South Square of the Yogyakarta Palace. The aim of this research is to analyze the influence of service quality and product quality on consumer satisfaction. This study uses a quantitative approach. The research sample consisted of 50 respondents from the population of MSME consumers with food and beverage products in the South Square area. The results of this research indicate that improving the quality of services and products can contribute positively to the level of consumer satisfaction. The managerial implication that can be implemented is that MSME food and beverage product operators located in the South Square of the Yogyakarta Palace can increase consumer satisfaction by improving the quality of the services and products they offer.